Transcriptome of Taenia solium during in vitro cyst activation and initial growth into the tapeworm stage - David Castaneda-Carpio; Renzo Gutierrez-Loli; Jose Maravi-Jaime; Segundo W. Del Aguila; Valeria Villar-Davila; Luz M. Moyano; Rafael Tapia-Limonchi; Stella M. Chenet; Cristina Guerra-Giraldez (Scientific Data)
Abstract The cestode Taenia solium develops as a tapeworm solely in the human intestine, starting from a larva (cyst). Upon maturing, it produces hundreds of thousands of infectious eggs. When ingested by pigs or humans, the eggs develop as cysts that lodge in various tissues, including the brain, leading to neurocysticercosis. Despite advances in understanding cestode biology through genomic and transcriptomic studies, particularly in model organisms, much remains unknown about the activation of T. solium cysts in the human digestive tract and the events that drive the development into adult worms—the stage responsible for dispersing the parasite. We present a transcriptome generated by Next Generation Sequencing from T. solium cysts activated in culture and collected at three different in vitro growth phases, defined by their morphology. Differentially expressed genes and biological processes relevant to activation and growth can be explored with the dataset. The information is valuable for identifying genes that regulate the molecular, metabolic, and cellular events leading to parasite maturation or elements driving its transmission.